Efektivitas dan Efisiensi Penggunaan Faktor Produksi Usahatani Cabai Besar di Desa Baturiti Kecamatan Baturiti Tabanan - SANGURJANA, I GEDE WEGANANDA FAJAR; WIDYANTARA, I WAYAN; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract The Effectiveness and Efficiency of The Usage of Production Factors in Chili Farming at Baturiti Village, Baturiti District, Tabanan Big c hili ( Capsicum annuum L. ) is a potential comm o dity of horticulture in Bali. One of chili producer areas in Bali is Baturiti village , Baturiti distric t, Tabanan regency. This study aims to find out the influ e nce of production factors, effectiveness and efficiency of usage of production factors to optimalizing production. The research was carried out at Baturiti village by analyzing production factors including the use of land, seed, fertilizer, pesticide, and labor using Cobb-Douglas production fu n ction. Data used in this study came from primary data of 56 respondents that were determined using random sampling method. The effectiveness of production factors use was examined from the comparison between marginal product and average product, while the efficiency of production factors was counted from comparison between marginal product value and production factors values. R esults of this research show that seed, NPK fertilizer , and labor affect total production, mean while land, urea fertilizer , ZA fertilizer , KCL fertilizer , TSP fertilizer , and pesticide do not affect. The use of production factors was ineffective because of the effe c tiveness was under 80 percent . The use of seed has not been efficient yet so that the amount of use can be increased, on the other hand the use of other production factors was inefficient consequently their use can be decreased. Keywords : Big c hili, production factor, effectiveness, efficiency